Method for the quantification of pharmaceuticals and personal care products - Zakaria, Mohamad Pauzi; Tan, Eugenie Sin Sing; Saari, Nazamid; Abdul Latif, Puziah (2012)

(untitled)
The present invention aims to develop a method for a more comprehensive group of PPCPs ranging from the most widely used to the most environmentally persistent as well as PPCPs with known ecological effects to aquatic organisms. These PPCPs must be quantified in APCI modes as low matrix suppressions are required. In addition, it aims to incorporate cost effective measures without compromising on the data quality. Sensitivity and selectivity shall not be compromised, thus, quantification must be carried out in multiple reaction monitoring (MRM) mode.